Pengaruh Model Pembelajaran Learning By Doing Terhadap Kemampuan Penalaran Siswa Di SMKS-PP Putra Jaya Jabal Rahmah Stabat - Khairunnisa, Isnaida, Ispandi Manurung (Pusdikra Publishing, 2019)
This study aims to determine the effect of the Learning By Doing model on the reasoning abilities of students in class X SMKS-PP Putra Jaya Jabal Rahmah Stabat, Langkat Regency. This research is a type of quasi-experimental research (quasi-experimental) with a nonequivalent control group design. The population in this study were all students of class X SMKS-PP Putra Jaya Jabal Rahmah with the determination of the sample through random sampling technique (random sampling). Based on this technique, obtained class X Livestock B as the experimental class and class X Plantation B as the control class. Each class consists of 34 and 35 students. Data collection techniques using test techniques, namely pretest and posttest. The validation used is Pearson correlation which shows the instrument is valid. Reliability test using Alpha Crobanch which shows a reliability index of 0.665 for the pretest instrument and 0.66 for the posttest instrument, which means both are reliable. Before analyzing the data, the normality test and homogeneity test were conducted which showed that the pretest and posttest scores were normally distributed and homogeneous. The data analysis technique used is linear regression test (F test) by comparing the Fcount value of 24.47 and F table of 7.56, then the Fcount> Ftable value is 24.47> 7.56. Thus, the results of the study indicate that there is a significant influence from the application of the learning by doing learning model on the reasoning abilities of Class X students of SMKS-PP Putra Jaya Jabal Rahmah in the subjects of Islamic religious education and character